Pembelajaran Digital Interaktif Multimodal Berbasis Netboard.Me Untuk Keterampilan Kolaborasi, Komunikasi, Dan Berpikir Kritis (3cs) - Muhamad Ruslan Layn; Arie Anang Setyo; Angelina Simangunsong (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research uses Netboard.me-based learning media with experimental research type, one-group pretest posttest design with quantitative descriptive methods which aims to measure how much influence Netboard.me-based multimodal interactive digital learning has in improving collaboration, communication and critical thinking skills. The data in this research was taken through pretest-posttest and non-test results in the form of observation sheets, self-assessment questionnaires and student responses. Based on the results of data analysis, it was found that students collaborated and communicated very well through observations, the self-assessment questionnaire got the highest results of 90% in giving, listening and supporting ideas, as well as sharing ideas and thoughts with others. Very good criteria are obtained in conveying opinions in writing clearly and concisely through a communication skills self-assessment questionnaire. Student responses to Netboard.me-based learning media obtained very very good criteria, namely 91% for interest and 95% for language use. Based on the results of the assessment of critical thinking skills indicators in the pretest and posttest results, students showed a significant increase in the average percentage of indicators. The N-Gain results obtained 59.2552% which is included in the quite effective category. The results of the two paired sample t-test show an increase in critical thinking skills through multimodal interactive digital learning based on netboard.me. So, interactive digital learning media based on Netboard.me can improve collaboration, communication and critical thinking skills